ЕВОЛЮЦІЯ ЕЛЕКТРОМАГНІТНИХ РЕЙКОВИХ ПРИСКОРЮВАЧІВ - Васьковський, Ю.М.; Райчев, П.О. (Інститут електродинаміки НАН України, Київ, 2021)
In the present article, the analytical overview of the worldwide modern approaches to the development of electromagnetic railguns (RG) was carried out. The major physical effects in the RG were analyzed, and the corresponding ways of increasing the RGs efficiency were showed up. Considering the wide range of the proposed ER configurations, their generalization and comparative analysis is highly needed. Thus, the comparison of the most advanced configurations of the ER - conventional RG, augmented, multi-turn, and multistage segmented RG was carried out. Finally, the variation of the multistage segmented RG, proposed by authors, has been described. This type of ER allows for the sufficient decrement of the ERs resistance by splitting the rails on mutually insulated segments, and commutating those segments without additional control equipment, but only by synchronized movement of the armature. References 15, figures 8.